Analisis Kebutuhan Bahan Pustaka Pengguna di UPT Perpustakaan Bung Karno Blitar Selama Masa Pandemi Covid-19 - Mudawamah, Siti; Prajawinanti, Arin (UI Scholars Hub, 2021)
The library is an information source institution that can meet the needs of library materials for the community. Different groups of people have different needs for library materials. This study aims to determine the needs of user library materials at the Bung Karno National Library UPT during the Covid-19 pandemic. This type of quantitative research uses descriptive research methods. The sampling technique used probability sampling with accidental sampling technique and obtained a sample of 50 respondents. Researchers collect research data through observation, questionnaires and literature study. The results of this study, that the characteristics of users are predominantly female (80%) and study as a student or college students (88%). The users of the Bung Karno National Library UPT used more information that was classified in the general collection. The reason users need information to add insight into new knowledge about a topic. Especially during a pandemic like today, what happens is that a lot of new things are emerging as innovations to keep all activities running. Although technology has developed rapidly, the source of library materials in the form of books is still an idol among the public because they are considered to have accurate information. Meanwhile, the reasons why UPT Bung Karno National Library users need library materials to help fulfill references in completing school and college assignments are 46%. In the condition of this online-based learning system, students are required to seek more independent references to meet their information needs. From the results of the study, it was also found that there were users who still did not know how to use information retrieval tools such as OPAC (Online Public Access Catalog) and also available technology. This is an obstacle in the process of meeting the needs of available library materials.